Design of a Novel Signed Binary Subtractor Using Quantum Gates - Banerjee, Arindam; Ghosh, Aniruddha; Das, Mainuck (Journal of quantum computing, 2022)
In this paper, focus has been given to design and implement signed binary subtraction in quantum logic. Since the type of operand may be positive or negative, therefore a novel algorithm has been developed to detect the type of operand and as per the selection of the type of operands, separate design techniques have been developed to make the circuit compact and work very efficiently. Two separate methods have been shown in the paper to perform the signed subtraction. The results show promising for the second method in respect of ancillary input count and garbage output count but at the cost of quantum cost.